2012
DOI: 10.1016/j.tet.2012.04.101
|View full text |Cite
|
Sign up to set email alerts
|

Application of chemoenzymatic hydrolysis in the synthesis of 2-monoacylglycerols

Abstract: The selective biocatalyzed synthesis of 2-monoacylglycerols (2-MAGs) through the use of commercially available immobilized Candida antarctica (Novozym435) and Rhizomucor miehei is explored. Reactions at room temperature result in the formation of a 2-MAG and a corresponding ethyl ester of the fatty acid with immobilized Candida antarctica within 2h with yields ranging from 36%–83%. Similar reaction conditions with immobilized Rhizomucor miehei yielded exclusively the 2-MAG after 24h with yields ranging from 37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…To the best of our knowledge the chemoenzymatic synthesis of this endogenous substance is reported here for the first time and parallels those we reported earlier for the endocannabinoid lipid 2-AG and its analogs. 33,34 Importantly, our approach provides the 2-PGE 2 -G essentially free of 1(3)-acylglycerol rearrangement byproducts as confirmed by 1 H NMR data. In a previous study on the metabolism of prostaglandin glycerol esters the 2-PGE 2 -G was the minor product which was synthesized as a mixture with the 1(3) regioisomer in a ratio 1:9.…”
Section: Resultssupporting
confidence: 55%
“…To the best of our knowledge the chemoenzymatic synthesis of this endogenous substance is reported here for the first time and parallels those we reported earlier for the endocannabinoid lipid 2-AG and its analogs. 33,34 Importantly, our approach provides the 2-PGE 2 -G essentially free of 1(3)-acylglycerol rearrangement byproducts as confirmed by 1 H NMR data. In a previous study on the metabolism of prostaglandin glycerol esters the 2-PGE 2 -G was the minor product which was synthesized as a mixture with the 1(3) regioisomer in a ratio 1:9.…”
Section: Resultssupporting
confidence: 55%
“…To date, 2-AG is synthesized by either chemical [16][17][18][19] or chemoenzymatic methods To date, 2-AG is synthesized by either chemical [16][17][18][19] or chemoenzymatic methods [20][21][22][23]. The chemical methods described for the synthesis of 2-AG are based on the same procedure: acylation of suitable 1,3-protected glycerol, or glycidol, precursors with an activated arachidonic acid derivative, followed by deprotection and separation of the isomeric arachidonoylglycerols.…”
Section: -Arachidonoylglycerol (2-agmentioning
confidence: 99%
“…The enzymatic methods described for the synthesis of 2-AG are based on a two-step enzymatic process [20][21][22][23]. 1,3-Dibutyrylglycerol is synthesized by selective esterification of glycerol, using vinyl butyrate in the presence of immobilized Candida antarctica lipase B and anhydrous dichloromethane as solvent.…”
Section: -Arachidonoylglycerol (2-agmentioning
confidence: 99%
“…A few methods have been developed for the synthesis of 2-MAG. However, acyl migration during reactions is the major impediment for the preparation of highly pure 2-MAGs. It has been reported that the ratio of 2-MAG to 1-MAG under equilibrium conditions is 1:9, suggesting that the spontaneous isomerization of 2-MAG will occur to form the more stable 1-MAG under certain conditions. , Acyl migration is a universal phenomenon during the alcoholysis and esterification with partial acylglycerols as a substrate or a product of the reaction.…”
Section: Introductionmentioning
confidence: 99%